Principal Criteria for Evaluating the Quality, Safety and Efficacy of hMSC-Based Products in Clinical Practice: Current Approaches and Challenges - Juan Antonio Guadix; Javier López-Beas; Beatriz Clares; José Luis Soriano-Ruiz; José Luis Zugaza; Patricia Gálvez-Martín (Pharmaceutics, 2019)
Human Mesenchymal Stem Cells (hMSCs) play an important role as new therapeutic alternatives in advanced therapies and regenerative medicine thanks to their regenerative and immunomodulatory properties, and ability to migrate to the exact area of injury. These properties have made hMSCs one of the more promising cellular active substances at present, particularly in terms of the development of new and innovative hMSC-based products. Currently, numerous clinical trials are being conducted to evaluate the therapeutic activity of hMSC-based products on specific targets. Given the rapidly growing number of hMSC clinical trials in recent years and the complexity of these products due to their cellular component characteristics and medicinal product status, there is a greater need to define more stringent, specific, and harmonized requirements to characterize the quality of the hMSCs and enhance the analysis of their safety and efficacy in final products to be administered to patients. These requirements should be implemented throughout the manufacturing process to guarantee the function and integrity of hMSCs and to ensure that the hMSC-based final product consistently meets its specifications across batches. This paper describes the principal phases involved in the design of the manufacturing process and updates the specific technical requirements needed to address the appropriate clinical use of hMSC-based products. The challenges and limitations to evaluating the safety, efficacy, and quality of hMSCs have been also reviewed and discussed.